Establishment of a Mesenchymal Stem Cell Bank. (4th August 2011) - Cooper, Khushnuma; Viswanathan, Chandra
Abstract : Adult stem cells have generated great amount of interest amongst the scientific community for their potential therapeutic applications for unmet medical needs. We have demonstrated the plasticity of mesenchymal stem cells isolated from the umbilical cord matrix. Their immunological profile makes it even more interesting. We have demonstrated that the umbilical cord is an inexhaustible source of mesenchymal stem cells. Being a very rich source, instead of discarding this tissue, we worked on banking these cells for regenerative medicine application for future use. The present paper gives a detailed account of our experience in the establishment of a mesenchymal stem cell bank at our facility.